Corrosion fatigue assessment and reliability analysis of short suspender of suspension bridge depending on refined traffic and wind load condition. (1st May 2021) - Liu, Xiaodong; Han, Wanshui; Yuan, Yangguang; Chen, Xiao; Xie, Qing
Highlights: Based on the Gaussian Mixture Mode and Expectation-Maximization algorithm, the measured traffic flow data are divided into four levels. A time-variant corrosion fatigue model of the wires is proposed by considering the wind load and stochastic traffic load with an annual growth. A refined load case which considers the wind load and stochastic traffic load with an annual growth is simulated in the corrosion fatigue analysis process. Abstract: Short suspenders in long-span suspension bridges are subjected to the coupled effects of corrosion by environmental media and fatigue by various cyclic live loads during operation. To study the influence of various load conditions on the corrosion fatigue process of short suspender wires, the refined load models are considered in the wind-vehicle-bridge system: a four-level traffic load model is developed based on the Gaussian Mixture Mode (GMM) and Expectation-Maximization algorithm (EM); a sampling method considering growing traffic is proposed; a mean wind speed model is built using field-monitoring data. The time-variant corrosion fatigue model which can consider the wind load and stochastic traffic load with an annual growth is developed, and the procedure to evaluate the reliability of the suspender wires of an in-service suspension bridge is conducted. The results indicate that the wires of short suspenders are prone to increased corrosion fatigue damage in a relatively sparse traffic flow, and a traffic load with an annual growth has a more significant influence on fatigue damage than the wind load. The lifespans and reliability indices of wires of short suspenders are significantly influenced by the values of the average growth ratio traffic load.